An outdoor temperature and global insolation model for Maracaibo - Almao de Herrera, Nastia (Revista Técnica da Faculdade de Engenharia da de Zulia)
Time dependent functions of outdoor temperature and global insolation over horizontal and vertical oriented planes are presented to be used in simulations of transient solar energy conversion processes under Maracaibo climatic conditions. A correlation to determine diffuse and beam components of the global insolation over horizontal planes is also presented. Deviations no higher than 12% were obtained for outdoor temperature. In reference to global insolation over horizontal planes, deviations from -5% to 8.7% were obtained at hours of higher insolation; and the values for vertical plane are not higher than 6.7% from sunrise time to peak insolation time, at which point from deviations start to increase. More accurate correlations were established via curve fit, however, deviations no higher than 0.8% were obtained when comparisons were made in a given solar energy conversion simulation. Therefore, the proposed correlations are recommended for simulation purposes.